2020
DOI: 10.3390/antibiotics9120864
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of OXA-Type β-Lactamase Genes among Carbapenem-Resistant Acinetobacter baumannii Clinical Isolates in Thailand

Abstract: Carbapenem-resistant Acinetobacter baumannii (CRAB) is a critical health concern for the treatment of infectious diseases. The aim of this study was to investigate the molecular epidemiology of CRAB emphasizing the presence of oxacillinase (OXA)-type β-lactamase-encoding genes, one of the most important carbapenem resistance mechanisms. In this study, a total of 183 non-repetitive CRAB isolates collected from 11 tertiary care hospitals across Thailand were investigated. As a result, the blaoxa-51-like gene, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…The findings of our study are consistent with those of an earlier report [ 25 ]. A. baumannii showed extensive drug resistance, and the diverse XDR strains had been reported by other studies [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 62%
“…The findings of our study are consistent with those of an earlier report [ 25 ]. A. baumannii showed extensive drug resistance, and the diverse XDR strains had been reported by other studies [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 62%
“…The prevalence of the bla oxa-23-like gene was found to be relatively high worldwide [ 5 , 24 , 25 ]. Thirapanmethee et al also reported that the OXA-23-like gene was the most common carbapenemase gene among CRAB clinical isolates in Thailand (68.31%) [ 26 ]. In addition, many new enzyme variants of OXA-24/40-like carbapenemases have been reported, including OXA-72.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Acinetobacter MLST database, some Thai ST2 clones and an ST215 A. baumannii clone have been present in the database since 2010, indicating local distribution over time [ 36 ]. Our previous work demonstrated that most carbapenem-resistant Acinetobacter baumannii isolates (CRAB) in Thailand were ST2 clones, but some belonged to ST25, ST98, ST129, ST164, ST215, ST338, and ST745 [ 26 ]. In Asia, ST2 has been reported as the most prevalent sequence type of CRAB in China and Lebanon [ 24 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediterranean counties have documented the emergence of A. baumannii belonging to ST2, with fewer identified isolates belonging to ST1. 41 , 42 A Lebanon study reported the detection of ST2 A. baumannii harboring NDM-1. 43 Several studies from Pakistan have described the detection of A. baumannii ST2 clones.…”
Section: Discussionmentioning
confidence: 99%